RANCANG BANGUN ANTENA MONOPOLE MIKROSTRIP MENGGUNAKAN DEFECTED GROUND STRUCTURE BENTUK PERSEGI UNTUK OPTIMASI BANDWIDTH PADA APLIKASI KOMUNIKASI ULTRA-WIDEBAND - M Darsono; Kafriyanti Kafriyanti (Jurnal Teknologi Terapan, 2023)
The development of UWB technology is very helpful in supporting high-speed data access. UWB offers a solution for large capacity for wide bandwidth. The frequency range for UWB systems between 3.1–10.6GHz will cause interference to wireless communication systems via wireless local area networks (WLANs) for IEEE 802.11a operating at 5.15–5.35GHz and 5.725–5.825GHz. This research aims to obtain a design of a rectangular printed monopole patch microstrip antenna and a slit using the Defected Ground Structure (DGS) technique to obtain bandwidth optimization on the UWB spectrum. For the implementation of the antenna design, the simulation method is used with the support of the RT/ Duroid substrate material. Realization of the design with the results of a manufactured antenna prototype with a minimalist size. The simulation and measurement results of the Absolute UWB bandwidth parameter at return loss < -10 dB (VSWR <2) the measurement value is 600MHz narrower than the simulation and for fractional bandwidth the measurement value is narrower by 0.21%. Resonance at the 5.2GHz frequency produces polarization with a gain value of 3.29dBi, omnidirectional and vertical polarization. As a prototype antenna to support the application of indoor wireless access communication devices that are low profile, compact with minimalist dimensions.